Factors Affecting the Strength of Denture Repairs - Rosangela Seiko Se´o, DDS, MSc;1 Karin Hermana Neppelenbroek, DDS, MSc;1 (Journal of Prosthodontics, 2007)
Fracture of dentures is a common clinical finding in daily prosthodontic practice, resulting in great inconvenience to both patient and dentist